Lateral cervical fibroid: a case report with review of literature - Hota, Basanta M.; Geetha, Lokam; Prashanthi, Chintirla G.; Maneesha, Kurapati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Cervical fibroid constitutes 1-2% of total fibroids and is usually solitary as the cervix is deficient in myometrium. It is classified into anterior, posterior, lateral, and central depending on its location. Being estrogen dependent, it is common in the reproductive age group. Lateral cervical fibroids constitute 10.26% of total cervical fibroids as reported by one retrospective observational cohort study. Symptoms of lateral cervical fibroid are vague and depend on its site and size. Chronic pelvic pain, dyspareunia, abnormal vaginal bleeding, and pressure effect on bowel in a left-sided lesion are the usual symptoms in a lateral cervical fibroid. As it grows into the broad ligament, compression of the ipsilateral ureter with renal affection is early. The patient’s obstetric outcome is likely to be affected. Pressure on pelvic vessels may cause hemorrhoids and edema in the legs. Growth and extension of this fibroid into the broad ligament distorts pelvic anatomy. Its definitive management is surgery, which is very challenging to the surgeon, with increased risk of ureteric damage and excessive hemorrhage. We report a case of lateral cervical fibroid of 08.5×05.0 cm with constipation, and menorrhagia; foul-smelling vaginal discharge and post-coital bleeding in a 38-year-old parous lady. Total abdominal hysterectomy with bilateral salpingectomy and right oophorectomy was done under regional anesthesia. Histopathological examination confirmed the diagnosis of right lateral cervical leiomyomas, sub-mucous fibroid polyp in the uterus, and excluded malignancy. The surgery was uneventful, and the patient remained asymptomatic and healthy during postoperative follow-up. Although the incidence is low, lateral cervical fibroids are more likely to distort the pelvic anatomy around important viscera, affecting other systems early, and surgery is challenging.